Child poverty in Malaysia: what do Malaysians think. - Jamaiudin, Norhaslinda; Mahmud, Maziah (UiTM Cawangan Negeri Sembilan, Kampus Seremban, 2021)
Child poverty is a prevailing issue in Malaysia. The report published by UNICEF in 2018 on the status of child poverty in Malaysia signals much-needed reform in the poverty alleviation program. The report disclosed the conditions of children who are living without sufficient amount of food, lack of nutritious food, proper shelter and some of them are not able to go to school (The Star, 2018). Accordingly, 99.7 per cent of children in low-cost flats live in relative poverty and 7 per cent in absolute poverty; about 15 per cent of children below the age of five are underweight, about 22 per cent of the children are stunted and only 50% of 5 to 6-year-olds attend pre-school enrolment (UNICEF, 2018). Child poverty shall not be perceived as a minor concern hence living in a poor household is detrimental to children’s educational attainment and development. As such it is pertinent for the government to re-assess their poverty policy measures and call for a rigorous drive to alleviate child poverty by developing programs exclusively targeted to children.